Does Regionalism Work in Managing the COVID-19 Pandemic: a Case Study of ASEAN - Casandra Aleksia (Indonesian Social Work Consortium (ISWC), 2023)
This article attempts to examine ASEAN’s response to and recovery from the COVID-19 pandemic, including through the implementation of the ASEAN Comprehensive Recovery Framework (ACRF). It is aimed to contribute to the existing literature by providing an applicable and valuable research on policy analysis by addressing the existing research evidence and the current research gaps on the response to the COVID-19 pandemic at the regional level, as well as what ASEAN brings to the regional security and prosperity. Keywords: ASEAN, pandemic, recovery, regional, security